2012
DOI: 10.1103/physrevb.86.121106
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization group approach for the scattering off a single Rashba impurity in a helical liquid

Abstract: The occurrence of two-particle inelastic backscattering has been conjectured in helical edge states of topological insulators and is expected to alter transport. Here, by using a renormalization group approach, we provide a microscopic derivation of this process, in the presence of a time-reversal invariant Rashba impurity potential. We are able to prove that such an effect only occurs in the presence of electron-electron interactions. Furthermore, we find that the linear conductance as a function of temperatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
110
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 24 publications
7
110
1
Order By: Relevance
“…10 However, also deviations from perfect conductance have been observed in longer HgTe devices, 6,7,11,12 which could stem from, e.g., inelastic scattering mechanisms. [13][14][15][16][17][18] The effect of external magnetic fields have also been considered. 6,8,[19][20][21][22][23][24] The TI state in HgTe QWs was predicted by Bernevig, Hughes, and Zhang (BHZ) 25 by using a simplified k · p model containing states with S-and P -like symmetries, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, also deviations from perfect conductance have been observed in longer HgTe devices, 6,7,11,12 which could stem from, e.g., inelastic scattering mechanisms. [13][14][15][16][17][18] The effect of external magnetic fields have also been considered. 6,8,[19][20][21][22][23][24] The TI state in HgTe QWs was predicted by Bernevig, Hughes, and Zhang (BHZ) 25 by using a simplified k · p model containing states with S-and P -like symmetries, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The spin-dependent chemical potentials of electrons in the puddle may be obtained either by solving Eqs. (32) and (34) or by making use of the elastic distribution function (13) and integrating the difference F σ (x) − (−ε) over the energy.…”
Section: A Single Puddlementioning
confidence: 99%
“…[12], the authors suggested that the backscattering could result from a dephasing of electrons captured from the edge state into a quantum puddle with chaotically arranged scatterers, but they could not draw a definite conclusion about the relevance of this mechanism to actual experiments. Two-particle scattering on a defect with localized spin-orbit coupling in a presence of electron-electron interaction was also considered [13]. This process results in a backscattering of electrons in the edge states and a weak temperature dependence of the conductance only if the Luttinger parameter describing the electron interaction in the edge states is very close to the value K = 1/4.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in such systems is motivated by potential applications in spintronics [31][32][33] and quantum computation [34,35]. The properties under consideration are most often related to transport, partially because the explanation of the weak temperature dependence of the non-perfectly quantized conductance in long samples still represents an open and challenging issue, even though several scattering mechanisms have been inspected [36][37][38][39][40][41][42][43][44][45][46]. Much less emphasis has, on the other hand, been devoted to its local properties [47].…”
mentioning
confidence: 99%